2020
DOI: 10.1111/aos.14459
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of objective and subjective visual quality early after implantable collamer lens V4c (ICL V4c) and small incision lenticule extraction (SMILE) for high myopia correction

Abstract: Purpose To investigate differences in the objective and subjective visual quality of patients with high myopia following implantable collamer lens V4c (ICL V4c) versus small incision lenticule extraction (SMILE) early postoperatively. Methods This prospective analysis included 94 eyes of 57 patients (8 males) in the ICL V4c group (mean spherical equivalent (SE), −8.07 ± 1.03 dioptres (D)) and 103 eyes of 57 patients (13 males) in the SMILE group (mean SE, −7.85 ± 0.78 D). Refractive parameters and wavefront ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 33 publications
7
51
0
Order By: Relevance
“…In this study, the main visual disturbances were starburst, halo, and vision uctuation two years after the surgery. These symptoms were not reported to disturb patients' daily life except for inconvenience when driving at night postoperatively, which is consistent with the ndings of Wei et al [19] Our study has some limitations. First, we observed only the changes in the corneal aberrations, whereas the effect of total ocular aberrations on visual quality was not analyzed.…”
Section: Postoperative Subjective Visual Quality and Patient Satisfactionsupporting
confidence: 91%
“…In this study, the main visual disturbances were starburst, halo, and vision uctuation two years after the surgery. These symptoms were not reported to disturb patients' daily life except for inconvenience when driving at night postoperatively, which is consistent with the ndings of Wei et al [19] Our study has some limitations. First, we observed only the changes in the corneal aberrations, whereas the effect of total ocular aberrations on visual quality was not analyzed.…”
Section: Postoperative Subjective Visual Quality and Patient Satisfactionsupporting
confidence: 91%
“…This agrees with that indicated by Wan et al [ 17 ] (size and orientation of the corneal incision) and Pérez-Vives et al [ 26 ] (tilt and decentration). Specifically, Wei et al [ 19 ] reported a mean value of 0.26 ± 0.07 μm for a 5.0-mm pupil, which was about half to that reported by Qin et al [ 16 ]. However, it must be pointed out that the mean SE in the study of Qin et al [ 16 ] was larger (about − 14 D) than that reported by Wei et al [ 19 ] (about − 8 D).…”
Section: Discussionmentioning
confidence: 84%
“…Wei et al [ 19 ] measured the optical quality in 94 eyes using the WASCA aberrometer at 6 months postsurgery. These authors reported a significant increase of HOAs after the surgery ( P < 0.05) indicating that this increase might be caused by the procedure itself or the innate optical properties of the lenses.…”
Section: Discussionmentioning
confidence: 99%
“…Through the continuous development and improvement in ICL implantation technology, the EVO-ICL implant with a central hole has become the most mainstream surgical method for intraocular refractive surgery, favoured by patients with high myopia and other refractive errors who are not satis ed with or do not qualify for corneal laser surgery [20] . The safety and e cacy of ICL implantation have been widely recognised [3,12] . During standard ICL implantation procedures, OVDs should be injected into the ICL implant container and the eyes to reduce the potential for damage to the corneal endothelium and transparent lens and to maintain the AC space for surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Visian ICL TM (STAAR Surgical, Nidau, Switzerland) is a type of posterior chamber PIOL [2][3] , and previous studies have shown that EVO-ICL (an implantable collamer lens with a centre hole) implantation is satisfactorily safe [4] . EVO-ICL implantation can reduce the induction of high-order aberrations and improve contrast sensitivity [5] .…”
Section: Introductionmentioning
confidence: 99%